E.P. Kazakov on the history and culture of the Volga Finns in the Middle Ages - Tatyana B. Nikitina (Археология евразийских степей, 2025)
The article summarizes the scientific conclusions and individual statements of E.P. Kazakov concerning the culture and history of the Volga Finns in the Middle Ages. According to E.P. Kazakov, the Volga peoples had a bright original culture different from the Bolgar one, and unlike the Ugric population, did not participate in the ethnic genesis of the Bolgars, therefore they were studied in the context of interaction with the Bolgars in the field of cultural, economic and trade spheres within the the periodization of the history of Volga Bolgaria. The early stage of the relationship between the Volga Finns and the Volga Bolgars is characterized by passivity. The flourishing of these relations occurred from the the X – beginning of the XIII centuries and was linked to the development of crafts in Volga Bolgaria and the increased activity of Bulgar merchants. Trade contacts were bilateral in nature: supplying the Volga Finns with a significant amount of various goods, the Bolgars bought, in addition to furs and hunting products, various jewelry. Considering that the decorations of the Finno-Ugric appearance were not used by the Bolgars for their intended purpose, E.P. Kazakov concludes that there are no ethnic-level contacts. The researcher also notes, starting from the second stage, numerous instances of Finno-Ugric population migration into the territory of Volga Bolgaria. Many of the author's conclusions are confirmed and supplemented by contemporary research.